Type of Verbal and Non-Verbal Reinforcement Given by Teacher in Elementary School (Journal of Primary Education, 2018)
The study aimed to analyze the form of reinforcement which given by teachers on its implementation in elementary school. This qualitative study uses data collecting technique in the form of observation and interview. The data were analyzed by using triangulation method. The results showed that there were two forms of reinforcement given by teachers in elementary school, namely verbal and non verbal reinforcements. Verbal reinforcement consists of 3 forms, namely: the form of verbal reinforcement of word, phrase, and sentence. The form of verbal reinforcement of word consists of 3 forms, namely: the form of verbal reinforcement of the numeral word, adjective, and interjection. The form of verbal reinforcement of phrases consists of 2 forms, namely: verbal reinforcement of verbal phrase and adjective phrase. The form of verbal reinforcement of sentence consists of 3 forms, namely: the form of verbal reinforcement of news sentence, command sentence, and interjection sentence. The reinforcement form that is often provided by the teacher in its implementation ofthe Elementary School is a form of non verbal reinforcement.